Windrowing and fuel-chip quality of residual forest biomasses in northern Sweden - Fernandez Lacruz, Raul; Bergström, Dan (International Journal of Forest Engineering, 2017)
Utilization of forest residual biomasses, including logging residues (LR) and whole tree-parts (WT), in Fennoscandia is expected to increase in response to increases in demand from the bioeconomy. LR and WT are often seasoned in windrows at roadsides, and more knowledge (prior to comminution) of their dry mass content would be highly useful for logistic planning and value estimations. Therefore, we have described and compared windrow fuel-chip quality and storage conditions of LR and WT delivered in one season to the same energy plant by the same supplier. A total of 76 windrows in northern Sweden were surveyed and chipped and 25 were also sampled to assess their moisture content (MC), ash content (AC) and particle size distribution. The mean MC (45%) did not significantly differ between LR and WT, but varied substantially within and between sites. LR fuel-chips had higher AC than WT (2.4% vs. 1.5%) and two-fold higher proportions of fines and oversized fractions (12.2 vs. 5.8% and 2.2 vs. 1.1%, respectively). LR windrows fully exposed to ambient conditions had 6.7% lower MC (43%) than sheltered counterparts. Average bulk densities of LR and WT were 66 and 59 dry kg per bulk cubic meter, respectively. The results enable development of models for estimating LR or WT windrows’ dry mass contents, show effects of some storage conditions on MC, and highlight the need for holistic supply chain management for cost-effective delivery of high-quality residual forest biomasses.